2018
DOI: 10.15517/revenf.v0i35.31519
|View full text |Cite
|
Sign up to set email alerts
|

Impacto dos fatores associados à sintomatologia depressiva na saúde de idosos em hemodiálise

Abstract: O objetivo desse estudo é conhecer o impacto dos fatores associados à sintomatologia depressiva na saúde de idosos em hemodiálise. Trata-se de uma revisão integrativa realizada em junho de 2017 com artigos selecionados por meio da Biblioteca Virtual em Saúde. Foram utilizadas duas combinações de descritores. A primeira foi: Associação; Depressão; Idoso e Diálise Renal. Em seguida, utilizou-se a segunda combinação: Depressão; Diálise renal e Idoso, fazendo-se uso da inter-relação do operador booleano and. Os cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
7
0
3
Order By: Relevance
“…Este estudo desenvolveu-se por meio de uma revisão integrativa, a qual permite, por meio de distintas metodologias, de acordo com que assinalam Souza;Carvalho (2010), uma atualização sobre a temática.…”
Section: Métodosunclassified
“…Este estudo desenvolveu-se por meio de uma revisão integrativa, a qual permite, por meio de distintas metodologias, de acordo com que assinalam Souza;Carvalho (2010), uma atualização sobre a temática.…”
Section: Métodosunclassified
“…Among these, 58% were male and 66.4% were in the age range from 19 to 64 years. 10 Due to the increased life expectancy and, consequently, the population aging, there is increase in prevalence and incidence of Chronic Noncommunicable Diseases (CNCD), such as Arterial Systemic Hypertension (ASH) and Diabetes Mellitus (DM). They are diseases scientifically considered as the main etiologies of CRF and risk factors for its progression.…”
mentioning
confidence: 99%
“…They are diseases scientifically considered as the main etiologies of CRF and risk factors for its progression. 6,10 In recent years, the worldwide prevalence of CRF requires increasing attention healthcare systems and professionals, because the pathology associates directly to a high rate of morbidity and therapies that significantly burden the budget and health care in many institutions worldwide. [11][12][13] Moreover, health care to the user diagnosed with CRF constitutes one of the main actions of high complexity of the Unified Health System (UHS) and is responsible for consuming high financial values intended to ambulatory care, 12 around 10% of the budget of the Ministry of Health.…”
mentioning
confidence: 99%
“…1 It is reported that, in general, the kidneys have endocrine, tubular and glomerular functions and play an essential role in the excretion of nitrogenated slag, guaranteeing the hydroelectrolytic balance and executing other actions that promote and maintain body homeostasis. 2 Due to the increase in life expectancy and, consequently, the population aging, there is a significant increase in the incidence rates of chronic diseases, such as systemic arterial hypertension (SAH) and Diabetes Mellitus (DM) [3][4] which constitute the two main pathologies involved in the genesis of chronic kidney failure (CKF), 3,5 a pathological condition in which slow, progressive and irreversible loss of renal function occurs. 2,6 It is mentioned that when the individual is diagnosed with end-stage CRF, it is necessary to submit it to one of the dialysis modalities to promote body homeostasis and, consequently, the maintenance of life.…”
mentioning
confidence: 99%
“…2,[5][6] It is reported that in HD, filtration and blood clearance occurs extracorporeally through a semipermeable membrane that integrates the hemodialysis device. 3,7 In PD, these processes are performed by infusing specific solutions in the peritoneal cavity that, through the peritoneum membrane, promotes diffusion, ultrafiltration and convection. These modalities have a significant impact on public health, 1 in social and economic terms, 8 although there are reasons that PD has low cost in relation to HD.…”
mentioning
confidence: 99%